Isotopic effects on in-plane hyperbolic phonon polaritons in MoO3 - Schultz Jeremy F.; Krylyuk Sergiy; Schwartz Jeffrey J.; Davydov Albert V.; Centrone Andrea (Nanophotonics, 2024)
Hyperbolic phonon polaritons (HPhPs), hybrids of light and lattice vibrations in polar dielectric crystals, empower nanophotonic applications by enabling the confinement and manipulation of light at the nanoscale. Molybdenum trioxide (α-MoO3) is a naturally hyperbolic material, meaning that its dielectric function deterministically controls the directional propagation of in-plane HPhPs within its reststrahlen bands. Strategies such as substrate engineering, nano- and hetero-structuring, and isotopic enrichment are being developed to alter the intrinsic dielectric functions of natural hyperbolic materials and to control the confinement and propagation of HPhPs. Since isotopic disorder can limit phonon-based processes such as HPhPs, here we synthesize isotopically enriched 92MoO3 (92Mo: 99.93 %) and 100MoO3 (100Mo: 99.01 %) crystals to tune the properties and dispersion of HPhPs with respect to natural α-MoO3, which is composed of seven stable Mo isotopes. Real-space, near-field maps measured with the photothermal induced resonance (PTIR) technique enable comparisons of in-plane HPhPs in α-MoO3 and isotopically enriched analogs within a reststrahlen band (≈820 cm−1 to ≈972 cm−1). Results show that isotopic enrichment (e.g., 92MoO3 and 100MoO3) alters the dielectric function, shifting the HPhP dispersion (HPhP angular wavenumber × thickness vs. IR frequency) by ≈−7 % and ≈+9 %, respectively, and changes the HPhP group velocities by ≈±12 %, while the lifetimes (≈3 ps) in 92MoO3 were found to be slightly improved (≈20 %). The latter improvement is attributed to a decrease in isotopic disorder. Altogether, isotopic enrichment was found to offer fine control over the properties that determine the anisotropic in-plane propagation of HPhPs in α-MoO3, which is essential to its implementation in nanophotonic applications.